KONSEP HIDUP KAYA DAN BERKAH - H.A. Yunus (MADINASIKA, 2019)
Having a dream to live rich is natural and natural, but in realizing it requires a strong theological conviction. Islam does not forbid rich life, but the good of the world and the hereafter is a priority. There are two important aspects in realizing the ideals, namely: a) The moral-religious aspects, including respect for parents, especially mothers; equating intentions and dreams with a partner; and give thanks to parents. b) Practical-empirical aspects, including simple living and fond of saving; have a side business that is cultivated as well as the profession; and likes to share. The concept of rich life is not measured by possessions, but is seen from its distribution according to God's provisions. Having lots of money can't be called rich if you can't share. The nature of rich life is rich is to have wealth and if there is an excess of the necessities of daily life want to share, especially zakat. Blessing cannot be seen in plain sight, but only felt by the owner, because blessing is filled with divine values for the good of the afterlife. In conclusion, rich life is not measured by abundance, but is determined by the sincerity of sharing in accordance with religious teachings. Blessing is felt by the owner of the treasure in the form of peace of mind and peace of life.